Factors affecting diabetes related hospitalization and in-hospital outcomes of adults with diabetes in south Ethiopia: A prospective observational study - Nigist Birhanu; Girma Mamo; Girum Sebsibe shiferaw; Daniel Gizachew; Firehiwot Belayneh; Temesgen Birhanu (PLoS ONE, 2025)
Background and objective Globally, diabetes mellitus is emerging as one of the most common chronic illnesses, and its prevalence has been increasing in the last decades. International Diabetes Federation reports that the number of people with diabetes in Ethiopia is 1.7 million. The prevalence of diabetes mellitus in Ethiopia is rising, and it is expected to increase to 2,031,000 in 2030. Diabetic patients have frequent hospitalization, which is associated with increased morbidity and mortality. The objective of this study was to assess reason for hospitalization and predictors for diabetes related hospitalization and in-hospital treatment outcome of adults with diabetes mellitus in Dilla University, a referral hospital in South Ethiopia. Method A hospital-based prospective observational study was conducted at medical, emergency, COVID-19 treatment center, and intensive care unit wards of Dilla University Referral Hospital from September 1, 2020, to May 30, 2021. All adult patients with diabetes mellitus who met the inclusion criteria were consecutively included in the study and followed until discharge or referral or death. To identify the predictors for in-hospital treatment outcome and diabetes related admission, logistic regression was run. Variables with p-value ≤ 0.05 on multivariate regression were considered statistically significant. Results A total of 153 patients were enrolled in the study. Diabetic ketoacidosis was the commonest reason for hospitalization (32%), followed by infection (22.2%) and cardiovascular diseases (9.2%). COVID-19 is the major cause of infection-related admission (13.7%). The mean length of hospital stay was 9.92 ± 7.97 days, ranging from 2 to 50 days. Higher proportion were discharged with improvement(71.9%) while 15.7% were self-discharge and 12.24% died in the hospital, mainly due to infections. The presence of comorbidity (AOR = 3.27, 95% CI: 1.39–7.68), obesity (AOR = 3.93, 95% CI: 1.42–10.9), patients with age group of 50–59 (AOR = 0.13, 95% CI: 0.03–0.56), ≥ 60 (AOR = 0.06, 95% CI: 0.018–0.25), and knowledge about diabetic foot ulcer complication (AOR = 0.33, 95% CI: 0.12–0.89) were predictors of diabetes-related admission. Regarding treatment outcome, poor exercise practice (AOR = 2.41, 95% CI: 1.014–5.77, p = 0.046), hypertension (AOR = 3.17, 95% CI: 1.39–7.19, p = 0.006), unsatisfactory knowledge about DM (AOR = 3.5, 95% CI: 1.12–10.9, p = 0.030), and being unmarried (AOR = 3.34, 95% CI: 1.47–7.58, p = 0.004) were predictors of poor treatment outcome. Conclusion Generally, this study showed that hyperglycemic emergencies, infections, and cardiovascular diseases were the most common reasons for hospitalization. The mortality rate is high, which is 12.24%, and urges attention to the care of hospitalized patients. Health care professionals should strengthen patient education on glycemic control and self-care practice, since the majority of patients have poor self-care practice and poor metabolic control.